Somatosensory Information Processing in the Aging Population - Zhang, Zheng; Francisco, Eric M.; Holden, Jameson K.; Dennis, Robert G.; Tommerdahl, Mark (Frontiers in Aging Neuroscience, 2011)
While it is well known that skin physiology – and consequently sensitivity to peripheral stimuli - degrades with age, what is less appreciated is that centrally mediated mechanisms allow for maintenance of the same degree of functionality in processing these peripheral inputs and interacting with the external environment. In order to demonstrate this concept, we obtained observations of processing speed, sensitivity (thresholds), discriminative capacity and adaptation metrics on subjects ranging in age from 18 to 70. The results indicate that although reaction speed and sensory thresholds change with age, discriminative capacity and adaptation metrics do not. The significance of these findings is that similar metrics of adaptation have been demonstrated to change significantly when the central nervous system (CNS) is compromised. Such compromise has been demonstrated in subject populations with autism (Tannan et al., 2008; Tommerdahl et al., 2007a), chronic pain (Hollins et al., 1996; Hollins and Sigurdsson, 1998; Zhang et al., 2011), acute NMDA receptor block (Folger et al., 2008) and with tactile-thermal interactions (Zhang et al., 2009). Thus, these quantitative measures – since they can be obtained efficiently and objectively, and appear to deviate from normative values significantly with systemic cortical alterations – could be useful indicators of cerebral cortical health.